Global and regional capital mobilities in Sub-Saharan African economies: Complement or substitute? - Taofeek Olusola Ayinde; Olumuyiwa Ganiyu Yinusa; Yulia Rodionova (SPOUDAI - Journal of Economics and Business, 2018)
This study examines the complementarity or substitutability of regional capital mobility to global capital mobility within the Sub-Saharan African (SSA) economies. With a re-specified inter-temporal consumption framework, the savings-investment correlation of the Feldstein-Horioka (hereinafter FH) hypothesis was revisited for a panel of eighteen (18) countries. The period of investigation spanned the period 1995 - 2016 and a battery of conventional and extended cum robust estimations tests and techniques were employed. The long-run correlation of savings and investments were investigated with the use of robust Pedroni and Westlund Cointegration tests while the short-run dynamics was examined with the Panel ARDL-ECM technique. With a confirmation of the long-run co-movement among the variables, the results obtained suggest that domestic investments in SSA economies are significantly and substantially financed by global savings. This implies that global integration has increased in the sub-region and that the FH hypothesis is validated. More so, the complementarity of regional capital mobility in the sub-region was evident. In fact, these results were found robust to a barrage of panel estimations techniques employed. However, both the level of financial development and the legal/political guidelines on capital mobility were found negligible to the level of domestic investment in the sub-region.
Keywords: E21; E22; F15; F21; 330; Savings; Investment; Economic Integration; Long-Term Capital Movement